Hubungan Regulasi Diri dan Stres Akademik dengan Prokrastinasi Akademik pada Mahasiswa Fakultas Psikologi Universitas Medan Area - Ayu Arwina; Risydah Fadilah; Abdul Murad (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
The purpose of this study is to examine the correlation between self regulatiom and academic stress with academic procrastination of College Students Faculty of Psychology batch 2015 and 206, Medan Area University. The approach used in this study is a quantitative approach. The samples technique in this study was an accidental sampling. In this study, the researcher used three scale measuring as the instrument type. The scale used to measure the academic procrastination, self regulation and academic stress scale. The data analysis techniques used in this study is a multiple regression analysis. Based on the analysis of data the results show that: (i). There is a negative significant relationship between self regulation with academic procrastination which was seen from R= -0496 and R2=0,246 where p < 0.05. (ii). There is a negative significant relationship between academic stress with academic procrastination which is seen from R= -0,452 and R2=0,204 where p < 0.050. (iii). There is a significant relationship between self regulation and academic stress with academic procrastination which is seen from coefficient value of R2=0,268. It means that there was a significant correlation self regulation and stress academi with academic procrastination college students Faculty of Psychology batch 2015 and 2016, Medan Area University.